Perbedaan Ketidaktepatwaktuan Penyampaian Laporan Keuangan Tahunan Terhadap Return Saham Pada Perusahaan Manufaktur di Bursa Efek Indonesia - Elna Marsye Pattinaja (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2023)
This study aims to determine whether the market reacts to untimely events. This study uses quantitative research methods with the selection of samples in this study using a purposive sampling technique. The results of the study show that the market reacts significantly to the untimely submission of issuer's financial reports. This is indicated by the significant difference in the abnormal returns on stock of issuers who are late, on time and submit their financial reports early. The results of the post hoc test with LSD show that earlier submission of financial reports gets the best market response from investors, or in other words has the highest abnormal returns. The limitations contained in the results of this study are based on a relatively small number of data sets and short observation times (only two years). As for suggestions that can be put forward, namely, 1) for investors who will buy shares, it is better to choose shares from issuers that historically have often or always submitted their financial reports earlier than Bapepam's provisions. This is because the shares of these issuers tend to be more able to provide high abnormal returns to shareholders. 2) For other researchers who are interested in conducting a review of this research, they should be able to carry out development steps in such a way that research results are better and more comprehensive. This development step can be carried out, for example, by adding observation time